1990
DOI: 10.1017/s0016672300025325
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic drive in female mice heterozygous for the HSR inserts on chromosome 1

Abstract: SummaryChromosome 1 with one or two long insertions has been previously found in natural mouse populations. The inheritance of chromosome 1 with two insertions from the Yakutsk population is analysed in this paper. It was demonstrated that heterozygous females transmit this chromosome to 80–85% of offspring. The observations made at M II, in conjunction with the recombination data, allowed us to conclude that preferential passage of the chromosome 1 with insertions to the oocyte and egg, rather than to the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 11 publications
1
38
0
1
Order By: Relevance
“…The wide distribution of SNPs with significant TRD must be interpreted in the light that pigs were randomly sampled at an age of 6 weeks, and multiple biological mechanisms could contribute to these allelic departures up to this age. Sperm competition [i.e., the preferential transmission of one of the two alleles to the zygote (Agulnik et al 1990;Lyon 1991;Dyer et al 2007;Labbe et al 2013)] could have a role during the early stages of male gametogenesis and fertilization, although embryo or fetal failure (Wakasugi 1974) and differential viability during the first 6 weeks of life (Moore 2006) could also be responsible of TRD effects. Although heritabilities for embryo survival [0.04 (Gama et al 1991 (Casellas et al 2004)] are low in pigs, they provide compelling evidence that survival traits are regulated by genetic factors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The wide distribution of SNPs with significant TRD must be interpreted in the light that pigs were randomly sampled at an age of 6 weeks, and multiple biological mechanisms could contribute to these allelic departures up to this age. Sperm competition [i.e., the preferential transmission of one of the two alleles to the zygote (Agulnik et al 1990;Lyon 1991;Dyer et al 2007;Labbe et al 2013)] could have a role during the early stages of male gametogenesis and fertilization, although embryo or fetal failure (Wakasugi 1974) and differential viability during the first 6 weeks of life (Moore 2006) could also be responsible of TRD effects. Although heritabilities for embryo survival [0.04 (Gama et al 1991 (Casellas et al 2004)] are low in pigs, they provide compelling evidence that survival traits are regulated by genetic factors.…”
Section: Resultsmentioning
confidence: 99%
“…Some type or TRD can only be observed through one parent. Meiotic drive restricts to the female gamete because males show symmetric meiosis that results in four functional gametes (Agulnik et al 1990), whereas gamete competition restricts to males, at least in mammals . Within these contexts, the previous assumption of sex-independent TRD effects must be seen as wrong and, as a consequence, we should be extremely cautious when trying to implement the TRD model.…”
Section: Transmission Ratio Distortion Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, mean fitness is 1 Figure 1.-Sex-specific segregation distortion. This chart summarizes a detailed review of genetic systems in which segregation distortion in autosomes has been reported (Rhoades 1942;Cameron and Moav 1957;Loegering and Sears 1963;Maguire 1963;Rick 1966;Maan 1975;van Heermert 1977;Gropp and Winking 1981;Sandler and Golic 1985;Silver 1985;Lavery and James 1987;Agulnik et al 1990;Sano 1990;Foster and Whitten 1991;Lyttle 1991;Pardo-Manuel de Villena et al 2000). Each star corresponds to a particular haplotype (in italics) and its host organism.…”
mentioning
confidence: 99%
“…This is as true for heterochromatic insertions as it is for Rbs. Whereas in S. murinus the chromosome 7 insertion does not segregate abnormally, in the house mouse a heterochromatic insertion of chromosome 1 can be associated with segregation distortion (Agulnik et al, 1990).…”
Section: Fig 2 Test For Association Betweenmentioning
confidence: 93%